Genetic variations associated with telomere length affect the risk of gastric carcinoma. Issue 23 (5th June 2020) - Lili, Ma; Yuxiang, Fan; Zhongcheng, Han; Ying, Su; Ru, Chen; Rong, Xu; Jiang, Liu
Abstract : Abstract: This study aimed to further understand the role of relative telomere length (RTL) in susceptibility to gastric carcinoma (GC) and investigate the association between genetic polymorphisms in the telomere length related genes and GC risk. RTL was measured using the real-time quantitative polymerase chain reaction from 1000 patients and 1100 healthy controls. Genotyping was performed using the Agena MassARRAY platform. The statistical analysis was performed using the chi-square/ Welch T tests, Mann–Whitney U test, and logistic regression analysis. The association analysis of telomere length and GC showed that the RTL in the case group was shorter than in the controls, and the shorter RTL was associated with an increased risk of GC. The association analysis between telomere length related genes polymorphisms and genetic susceptibility to GC indicated that: In the allele models and genetic models, TERT (rs10069690, rs2242652 and rs2853676) and TN1F1 (rs7708392 and rs10036748) were significantly associated with an increased risk of GC. In addition, the haplotype "Grs10069690 Crs2242652 " of TERT and the haplotype "Grs7708392 Trs10036748 " of TNIP1 were associated with an increased risk of GC Our results suggested that shorter RTL was associated with an increased risk of GC; The association analysis have identified that the TERT (rs10069690, rs2242652 and rs2853676) and TN1P1 (rs7708392 and rs10036748) were associated with GC risk. Abstract : Supplemental Digital Content is available in the text